Technological contributions for health: Outlook on physical activity - Verzani, Renato Henrique [UNESP]; de Souza Serapião, Adriane Beatriz [UNESP] (FapUNIFESP (SciELO), 2020)
The scope of this paper sought to analyze the potential of using Internet technologies of wearable accessories and devices and the possible interventions in physical activities, seeking improvements with respect to physical inactivity and Chronic Non-Communicable Diseases (CNCDs). By means of a bibliographical review, it was revealed that there is great concern regarding physical inactivity and CNCDs as well as the increasing research focus on these technological strategies. The amount of data collected in real time is one of the strengths of the devices, which can assist in longitudinal research, interventions in patients and also in physical activities performed, revolutionizing relationships and interventions in the area.
Contribuições tecnológicas para saúde: Olhar sobre a atividade física
Keywords: Chronic Disease; Human Development; Physical education and training; Technological Development; Wearable Electronic Devices